"Now I Know I'm Not the Only one": A Group Therapy Approach for Adoptive Parents. Issue 1 (2nd January 2022) - Downes, Ciara; Kieran, Sara; Tiernan, Bridget
ABSTRACT: Many children who enter the care system and are subsequently adopted have had exposure to a range of potentially traumatising experiences including domestic violence, abuse, neglect and loss of key caregivers. There are also an increasingly high number of adopted children presenting with the impact of intrauterine exposure to alcohol, drugs and stress. They are often adopted by adults with their own experiences of loss and fertility difficulties. Despite the low overall level of adoption disruption, it is becoming clear that some adoptive parents may face difficulties in terms of forming and maintaining secure attachments across time with their children. A 9-week therapeutic group intervention was delivered to a group of 15 adoptive parents in Northern Ireland. This incorporated psychoeducation on a range of topics including attachment theory, trauma and the impact on brain development. It also incorporated theory and practical strategies for parenting therapeutically with traumatised children, and those with foetal alcohol and drug-related difficulties. The main focus of the group was on developing the capacity for mind-mindedness in the parents, through the more reflective focus of the second half of each group. The results from the evaluation indicated the positive impact of this intervention on parents' understanding of their children, increased confidence in parenting, and increased sense of competence in coping with challenging behaviour. It also indicated a positive change in the children's behaviour and in the parent-child relationships.